Deteksi Antibakteri Fraksi Ekstrak Etanol Folium Sambung Nyawa (Gynura procumbens) pada Salmonella typhi - Yosi Darmirani; Wibman Tambunan; Debi Meilani (Yayasan Penelitian dan Inovasi Sumatera, 2023)
Background: Folium Sambung Nyawa, a native plant in Indonesia, is known for its abundant medicinal properties. Among its various secondary metabolites, flavonoids stand out, being polyphenolic compounds found in numerous plants and foods. Flavonoids exhibit a wide range of bioactive properties, including antibacterial, anti-inflammatory, anti-diabetic, anti-cancer, anti-ageing, and antioxidant effects. Objective: This study aimed to assess the antibacterial potential of Sambung Nyawa Leaf extract fractions against Salmonella typhi bacteria. Methods: The antibacterial activity was evaluated using the paper disc diffusion method to determine the inhibition zones. Three fractions—n-hexane, ethyl acetate, and water—were tested at concentrations of 10%, 20%, and 30% each, along with negative controls (DMSO) and positive controls (Chloramphenicol). Results: Flavonoid examination using synode reagent yielded positive results. Among the fractions tested, the 30% ethyl acetate fraction exhibited the most promising antibacterial activity, with an inhibition zone of 7.65 mm, indicating strong efficacy against Salmonella typhi bacteria. Conclusion: The findings suggest that the ethyl acetate fraction of the concentrated Sambung Nyawa leaf extract possesses potent antibacterial properties against Salmonella typhi bacteria